Can TP53-mutant follicular adenoma be a precursor of anaplastic thyroid carcinoma?. Issue 9 (6th August 2021) - Nikitski, Alyaksandr V; Nikiforova, Marina N; Yip, Linwah; Karslioglu-French, Esra; Carty, Sally E; Nikiforov, Yuri E
Abstract : Mutations of the TP53 tumor suppressor gene are highly prevalent in thyroid anaplastic carcinomas (AC) but are also reported in some well-differentiated cancers and even in benign adenomas. The natural history of TP53- mutant adenomas and whether they may represent a precursor for well-differentiated cancer or AC is largely unknown. Similarly, the frequency of TP53 mutations in thyroid nodules found on routine molecular analysis of fine-needle aspiration (FNA) samples is not established. A database on 44, 510 FNA samples from thyroid nodules with predominantly indeterminate cytology tested using ThyroSeq v3 was reviewed to identify TP53- mutant cases and analyze their genetic profile and available clinicopathological findings. Among 260 (0.6%) selected thyroid nodules, 36 had an isolated TP53 mutation and 224 carried a combination of TP53 with other genetic alterations. No significant difference was observed between these groups with respect to patient age, gender, nodule size, and spectrum of TP53 mutations . Histopathologically, 86% of the resected nodules with isolated TP53 mutations were benign (mostly adenomas), whereas 82% of nodules carrying TP53 mutations co-occurring with other alterations were cancers ( P = 0.001), including de-differentiated AC. TP53 -mutant benign tumors and well-differentiated cancers often had scattered single neoplastic cells with bizarre nuclei resembling those comprising AC. Our study demonstrates that a small but distinct proportion of thyroid nodules carry a TP53 mutation, either as a single genetic event or in combination with other alterations. While the latter is mostly cancers prone to dedifferentiation, there is at least a theoretical possibility that TP53 -mutated adenomas may represent a precursor for such cancers, including AC.